Assessment of compliance with quality laboratory standards in medical laboratories within the Kumasi Metropolis, Ghana - Elizabeth Sorvor; Mawuli Dzodzomenyo; Justice Nonvignon; Genevieve Cecilia Aryeetey (PLoS ONE, 2026)
Background In Ghana, medical laboratories are a vital component of the health system, but there has been limited evidence on how well they meet international quality standards. This study assessed compliance with laboratory standards by medical laboratories in the Kumasi Metropolis of Ghana. Methods A descriptive cross-sectional survey was conducted among forty-three (43) laboratory facilities, including those operating within healthcare facilities and private standalone laboratories, in the Kumasi metropolis from 8th March to 26th November, 2021. The healthcare facilities assessed include seven (7) government, four (4) Christian Health Association of Ghana (GHAG), twenty-one (21) private hospitals, and eleven (11) standalone laboratories. The World Health Organisation Stepwise Laboratory Quality Improvement Process Towards Accreditation (WHO SLIPTA) checklist was used to assess compliance with laboratory standards. The checklist comprises 12 main sections, containing 117 questions, resulting in a total of 275 scores. Each item is awarded a point value of 2, 3, or 5 points based on relative importance and complexity. Scores and percentages of compliance are categorized as follows: 0–150 (<55%), 151–177 (55–64%), 178–205 (65–74%), 206–232 (75–84%), 233–260 (85–94%), and 261–275 (≥95%). These categories ultimately translate to a rating of 0–5 stars. Descriptive analysis and the Kruskal-Wallis test were conducted to examine the differences in overall compliance scores across the types of health facilities. Results The overall median compliance score was 61(interquartile range 53–66), the minimum score was 49, and the maximum score was 104. CHAG facilities had significantly higher scores than private facilities (Z = 2.53, p = 0.03) and standalone facilities (Z = 3.60, p < 0.001). Similarly, scores for government facilities were significantly higher than standalone facilities (Z = 3.30, p < 0.001). Conclusion All facilities had a zero (0) star rating and failed to meet the minimum compliance level of 55%.